KEBERLANJUTAN PROGRAM JAPFA FOR KIDS MELALUI KEGIATAN MENJAGA KEBERSIHAN DAN KESEHATAN LINGKUNGAN SEKOLAH YANG DILAKUKAN OLEH PT GAGAS INSPIRASI NUSANTARA - Kurnianingtyas, Nia; Anugrahini, Triyanti (Jurnal Pembangunan Manusia, 2021)
Sustainable Development Goals (SDGs) number 3 dan 17 provide guidance for the development of policies and programs to enhance children’s welfare and health, which could be implemented by a partnership between government and corporation. SDGs implicate the urgency to undertake program continuation for development programs. Japfa for Kids is one of the social development programs that undertake its program continuation. Japfa for Kids is a CSR program for PT Japfa Comfeed Indonesia, working to enhance students' clean and healthy behavior, especially for elementary students. This program has transformed itself from an event and charity-based program into a community development program and managed by PT Gagas Inspirasi Nusantara since 2017. Japfa for Kids in SDN Kemakmuran, Kota Cirebon, successfully developed sustainable (continuing) plastic waste reduction practices as part of activities to maintain a clean and healthy school environment. The purpose of this research is to describe Gagas’ strategies towards target communities to achieve Japfa for Kids program continuation through clean and healthy school environment activities resulted in plastic waste reduction practice. This research used qualitative descriptive research. Data were collected from in-depth interviews with twelve informants selected using purposive sampling. Data was also collected from the literature study. The result of this research demonstrates that Gagas used various strategies, from empowering and consciousness-raising of the school’s community, building community, building consensus, develop collaboration, develop policy and habituation, develop the system, involve control from external stakeholders, and develop an exit strategy. This research summarizes that research program continuation strategies towards target communities are interconnected strategies of non-directive approaches, implementing process principles, the institutionalization of changes, creating program sustainability, and developing exit strategy